Jenius : the amazing guinea pig / Dick King-Smith ; illustrated by Brian Floca. - King-Smith, Dick (Hyperion Books for Children, 1996)
Eight-year-old Judy tries to convince her parents and classmates that her brilliant guinea pig can do all the tricks which she says it can.
Keywords: Guinea pigs -- Juvenile fiction.; Schools -- Juvenile fiction.; Guinea pigs.; Schools.; Fiction.; Juvenile works.